Relationships between educational attainment, hypertension, and amyloid negative subcortical vascular dementia: The brain-battering hypothesis - Hwangbo, Song; Kim, Young Ju; Park, Yu Hyun; Kim, Hee Jin; Na, Duk L.; Jang, Hyemin; Seo, Sang Won (Frontiers in Neuroscience, 2022)
Purpose: Many epidemiological studies suggest that lower education levels and vascular risk factors increase the likelihood of developing Alzheimer’s disease dementia (ADD) and subcortical vascular dementia (SVaD). However, whether the brain-battering hypothesis can explain the relationship between education levels and the clinical diagnosis of dementia remains controversial. The objective of this study was to investigate whether vascular risk factors mediate the association between education level and the diagnosis of amyloid-positive ADD and amyloid-negative SVaD. Methods: We analyzed 376 participants with amyloid-negative normal cognition (NC), 481 with amyloid-positive ADD, and 102 with amyloid-negative SVaD. To investigate the association of education level and vascular risk factors with these diagnoses, multivariable logistic regression analysis was used, with age, sex, and APOE ε4 carrier status used as covariates. Path analysis was performed to investigate the mediation effects of hypertension on the diagnosis of amyloid-negative SVaD. Results: The amyloid-negative SVaD group (7.9±5.1 years) had lower education levels than did the amyloid-negative NC (11.8±4.8 years) and amyloid-positive ADD (11.2±4.9 years) groups. The frequencies of hypertension and diabetes mellitus were higher in the amyloid-negative SVaD group (78.4% and 32.4%, respectively) than in the amyloid-negative NC (44.4% and 20.8%) and amyloid-positive ADD (41.8% and 15.8%, respectively) groups. Increased education level was associated with a lower risk of amyloid-negative SVaD (odds ratio [OR] 0.866, 95% confidence interval [CI], 0.824-0.911), but not amyloid-positive ADD (OR 0.971, 95% CI 0.940-1.003). The frequency of hypertension was associated with a higher risk of developing amyloid-negative SVaD (OR 3.373, 95% CI, 1.908-5.961), but not amyloid-positive ADD (OR 0.884, 95% CI, 0.653-1.196). In the path analysis, the presence of hypertension partially mediated the association between education level and the diagnosis of amyloid-negative SVaD. Conclusion: Our findings revealed that education level might influence the development of amyloid-negative SVaD through the brain-battering hypothesis. Furthermore, our findings suggest that suitable strategies, such as educational attainment and prevention of hypertension, are needed for the prevention of amyloid-negative SVaD.